THE GEOLOGICAL RECORD OF THE OLDEST HISTORICAL TSUNAMIS IN SOUTHWESTERN SPAIN (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2008)
A regressive sequence was determined in the late Holocene evolution of the southwestern Doñana National Park (SW Spain), based on a multidisciplinary study of sediments obtained in a drill core. In an initial phase (> cal. 2400 years BP), a shallow coastal lagoon with a partial marine connection occupied this area, with a progressive transition from subtidal to supratidal conditions. The following phase (cal. 2400-2350 years BP) is characterized by a tsunami, with the deposition of an upper chenier. This sedimentological layer is characterized by a ridge morphology, an erosive base, high bioclastic contents and the introduction of marine species toward the inner areas of this old lagoon. This tsunami may be assimilated to one of the historical tsunamis that occurred between 218 and 209 BC. A comparison with other deposits derived from these high-energy events permits to draw the differential effects produced along the western Iberian coasts. SHORT NOTES
Keywords: Estuarine evolution; Tsunami deposits; Late Holocene; SW Spain; Portugal